Analysis of Street Lighting Tax Collection Procedures in the Regional Revenue Agency of North Minahasa District - Tumade, Meysi; Elim, Inggriani; Mintalangi, Syermi S. E. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Street lighting tax is a tax imposed on users of electricity, both self-generated and sourced from other sources. The study aims to determine the implementation and suitability of the collection procedures for ppj at BAPENDA North Minahasa. The purpose of this research is to find out how the implementation and suitability of the procedures for collecting Road Lighting Tax carried out at Bapenda Kab. North Minahasa. The research data source used primary data with descriptive qualitative research methods. The results showed that the implementation and suitability of road lighting tax collection procedures at BAPENDA were in accordance with applicable procedures both self-generated and sourced from electricity. From other sources where in the implementation of non-PLN collection procedures are collected by BAPENDA, while self-generated PPJ is collected by PLN.